Consumption Behavior Patterns of Muslim Students on The Decision of Buying Halal Culinary Fast Food in Surabaya - A. Fikri Amiruddin Ihsani; Novi Febriyanti (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
The purposes of this study was to analyze the consumption behavior patterns of the Postgraduate Students of UINSA Islamic Economics study program as consumers and supporting factors in purchasing halal culinary food products. The research method used was a qualitative research method with a phenomenological approach, this research observes 10 informants of the Postgraduate Students of Islamic Economics Study Program UINSA as fast food consumers KFC Ahmad Yani Surabaya. The results of this study prove that all informants have knowledge of the concepts of consumer behavior and halal products in Indonesia, especially in Surabaya. The students have also applied the pattern of Islamic consumption behavior that is tauhid, fairness, free will, responsibility and halal as well as supporting factors including cultural, social, personal and psychological factors. Knowledge about other supporting factors should be utilized by other consumers for the sustainability and development of perceptions about halal culinary fast food in Surabaya